EXTH-45. THE REPURPOSED CUSP9 REGIMEN EXERTS POTENT ANTI-NEOPLASTIC ACTIVITY AGAINST GLIOBLASTOMA CELLS IN VITRO. (5th November 2018) - Halatsch, Marc-Eric; Kast, Richard Eric; Dwucet, Annika; Siegelin, Markus; Heiland, Tim; Karpel-Massler, Georg
Abstract: OBJECTIVE: Drug repurposing is a strategy to safely accelerate the clinical application of therapeutics that provide anti-cancer activity. CUSP9 represents such a therapeutic regime which includes nine repurposed drugs along with low-dose temozolomide. In this work, we examined the biological activity of the CUSP9 regimen in an in vitro setting of glioblastoma. METHODS: MTT and soft-agar assays were used to examine cellular proliferation. Staining for Annexin V/PI and Western blotting were used to examine pro-apoptotic effects. A spheroid assay was performed to assess effects of the treatments on three-dimensional growth. Time-lapse microscopy, radius and transwell assays were performed to examine anti-migratory effects. RESULTS: Treatment with CUSP9 exerted profound anti-proliferative activity and inhibited anchorage-independent growth among a broad panel of established, primary cultured and glioma stem-like cells. These effects were accompanied by enhanced apoptosis as indicated by an increased fraction of Annexin V-positive cells and enhanced caspase-3 cleavage. Moreover, CUSP9 lead to significantly decreased 3-dimensional tumor formation. In addition, non-directed and directed movement of glioblastoma cells were significantly impaired following CUSP9 treatment. CONCLUSION: These data suggest that CUSP9 has potent anti-cancer activity in vitro which is currently further explored by a clinical trial being conducted at our institution (NCT02770378).